PEMUPUKAN UREA DAN PACLOBUTRAZOL TERHADAP PERTUMBUHAN TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt.) - Tumewu, Pemmy; Supit, Paula Ch.; Bawotong, Ridson; Tarore, Anni E.; Tumbelaka, Selvie (EUGENIA, 2012)
ABSTRACT The study aims to determine the response of sweet corn plants of urea fertilizer and the provision of Paclobutrazol. Randomized trials using Design Group (RAK) Factorial pattern. The experiments are a factor I (A): Nitrogen fertilizer, Ao = Without fertilization, A1 = 100 kg N / ha, A2 = 200 kg N / ha, and Factor II (B): The concentration of Paclobutrazol ie, Bo = Without Paclobutrazol, B1 = 500 ppm, B2 = 1000 ppm. Variables observed were: 1) Higher Plants, 2) The number of leaves. Data were analyzed using a variety of analysis followed by LSD 5%. The results showed that the interaction between nitrogen fertilizer and Paclobutrazol is not significant Â on sweet corn plants but interaction on the number of leaves. Paclobutrazol independently affect the height of sweet corn plants. Giving Paclobutrazol 500 ppm and 1000 ppm to corn plants are shorter than without Paclobutrazol. Keywords: Nitrogen fertilizer, Paclobutrazol, and sweet corn crops ABSTRAK Penelitian bertujuan untuk mengetahui respon tanaman jagung manis terhadap pemupukan urea dan Paclobutrazol. Percobaan acak menggunakan Design Group (RAK) pola faktorial. Percobaan adalah faktor I (A): pupuk Nitrogen e Ao = Tanpa pembuahan, A1 = 100 kg N / ha, A2 = 200 kg N / ha, dan Faktor II (B): Konsentrasi Paclobutrazol yaitu, Bo = Tanpa paclobutrazol, B1 = 500 ppm, B2 = 1000 ppm. Variabel yang diamati adalah: 1) Tanaman tinggi, 2) Jumlah daun. Data dianalisis dengan menggunakan berbagai analisis diikuti oleh Uji Perbedaan Terkecil Real (LSD) 5%. Hasil penelitian menunjukkan bahwa interaksi antara pupuk nitrogen dan Paclobutrazol tidak nyata pada tinggi tanaman jagung manis tapi interaksi nyata pada jumlah daun. Paclobutrazol mempengaruhi tinggi tanaman jagung manis. Pemberian Paclobutrazol 500 ppm dan 1000 ppm memberikan tanaman jagung lebih pendek daripada tanpa Paclobutrazol. Kata kunci: Pupuk nitrogen, Paclobutrazol, dan tanaman jagung manis